2017
DOI: 10.1186/s13071-017-2060-5
|View full text |Cite
|
Sign up to set email alerts
|

The physiological cost of male-biased parasitism in a nearly monomorphic mammal

Abstract: BackgroundEven though male-biased parasitism is common in mammals, little effort has been made to evaluate whether higher parasitic burden in males results in an extra biological cost, and thus a decrease in fitness. Body condition impairment and the augmentation of oxidative stress can be used as indicators of the cost of parasite infections. Here, we examined relationships between gastrointestinal and respiratory helminths, body condition and oxidative stress markers (glutathione peroxidase, paraoxonase-1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Byrne et al, ) and thus provide a proxy of the costs associated with different alternative reproductive tactics. A recent study, however, suggested that males may have developed natural mechanisms to compensate for higher parasite infection during the rut (Oliver‐Guimerá et al, ). If so, ARTs may not suffer different costs of parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…Byrne et al, ) and thus provide a proxy of the costs associated with different alternative reproductive tactics. A recent study, however, suggested that males may have developed natural mechanisms to compensate for higher parasite infection during the rut (Oliver‐Guimerá et al, ). If so, ARTs may not suffer different costs of parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…competition for resources among parasite species) only visible under a co-infection approach. The study of these interactions and the price of neglecting parasite group/species when addressing the cost of parasites to host fitness is gaining increasing attention in the disease ecology community [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…moose, Alces alces ) [ 26 ] or negative relationship (e.g. chamois, Dall’s sheep) [ 14 , 27 ] on the health and individual fitness of host with increased parasite richness were reported. This might be explained by the nematode community composition with different levels of pathogenicity among parasites, even among closely phylogenetically related species, and may have synergistic or antagonistic interactions [ 18 , 28 – 30 ].…”
Section: Introductionmentioning
confidence: 99%